Design of Student Worksheet Teaching Materials for Viscosity of Biodiesel, Dexlite, and Pertamina Dex with Falling Ball Measurement Technique - Lesmono, A. D.; Ramadhan, E. B.; Handayani, R. D.; Prastowo, S. H. B. (Jurnal Pendidikan Fisika Indonesia, 2023)
The lack of teaching materials use, especially in viscosity topics, has decreased students' knowledge and analytical skills in measurement. The research aimed to design a Student Worksheet (LKPD) for viscosity topics to assist and train students in measuring the viscosity of fluids. The fluids used in the experiment were biosolar, dexlite, and pertamina dex, considering that these fuels are among the most significant commodities and widely used in Indonesia. Additionally, the viscosity of diesel fuel is an important property affecting combustion and engine injection. This research employed a quantitative method using laboratory experiments to measure the viscosity values of biosolar, dexlite, and pertamina dex using the falling-ball method. The research findings were utilized to develop the LKPD teaching materials. The results showed that the viscosity values of biosolar fuel, dexlite, and pertamina dex were 3.651 cP; 3.579 cP; and 3.004 cP; respectively. These results differed slightly from the literature but were still deemed suitable for the LKPD teaching material design. The title of the LKPD teaching material used was "Viscosity of Biosolar Fuel, Dexlite, and Pertamina Dex Using the Falling-Ball Measurement Technique," and it followed the format of a cover, usage instructions, summary of the material, laboratory assignments, and questions.